Jane Eyre - Bronte, Charlotte (New York Black & White Classics, 2014)
The story of a plain and penniless orphan who accepts a job as governess at Thornfield Hall and soon finds herself in love with her melancholy employer, Mr. Edward Rochester, a man with a terrible secret.
"1847 Edition" on back of title page.
"1847 Edition, New York."
103755
Keywords: Governessess -- England; Young women -- England; England; Classic literature -- British